Efficacy of Er:YAG laser irradiation for decontamination and its effect on biocompatibility of different titanium surfaces - Peijun Huang; Xue Chen; Zhongren Chen; Min Chen; Jinzhi He; Lin Peng (BMC, 2021)
Abstract Background Erbium yttrium-aluminum-garnet (Er:YAG) laser have been shown to be suitable for decontamination of titanium surfaces at a wide range of energy settings, however, high intensity of laser irradiation destroy titanium surface and low intensity cannot remove enough microbial biofilm. The aim of this study was to investigate the optimal energy setting of Er:YAG laser for decontamination of sandblasted/acid-etched (SLA) and hydroxyapatite (HA) titanium surfaces. Material and methods After supragingival biofilm construction in vivo, SLA and HA titanium discs were divided into three groups: blank control (BC, clean discs), experimental control (EC, contaminated discs) and experimental groups (EP, contaminated discs irradiated by Er:YAG laser at 40, 70, and 100 mJ/pulse). Scanning electron microscopy (SEM), live/dead bacterial fluorescent detection, and colony counting assay were used to detect the efficacy of laser decontamination. To investigate the effect of laser decontamination on titanium surface biocompatibility, MC3T3-E1 cell adhesion and proliferation activity were examined by SEM and CCK-8 assay. Results Er:YAG laser irradiation at 100 mJ/pulse removed 84.1% of bacteria from SLA titanium surface; laser irradiation at 70 and 100 mJ/pulse removed 76.4% and 77.85% of bacteria from HA titanium surface respectively. Laser irradiation improved MC3T3-E1 cell adhesion on both titanium surfaces. For SLA titanium discs, 100 mJ/pulse group displayed excellent cellular proliferation activity higher than that in BC group (P < 0.01). For HA titanium discs, 70 mJ/pulse group showed the highest activity comparable to BC group (P > 0.05). Conclusions With regards to efficient microbial biofilm decontamination and biocompatibility maintenance, Er:YAG laser at 100 mJ/pulse and 70 mJ/pulse are considered as the optimal energy settings for SLA titanium and HA titanium surface respectively. This study provides theoretical basis for the clinical application of Er:YAG laser in the treatment of peri-implantitis.